On extrapolation of virial coefficients of hard spheres - Ončák, M.; Malijevský, A.; Kolafa, J.; Labík, S. (Condensed Matter Physics, 2012)
Several methods of extrapolating the virial coefficients, including those proposed in this work, are discussed. The methods are demonstrated on predicting higher virial coefficients of one-component hard spheres. Estimated values of the eleventh to fifteenth virial coefficients are suggested. It has been speculated that the virial coefficients, Bn, beyond B₁₄ may decrease with increasing n, and may reach negative values at large n. The extrapolation techniques may be utilized in other fields of science where the art of extrapolation plays a role. Обговорюються декiлька екстаполяцiйних методiв для вiрiальних коефiцiєнтiв, включно iз запропонованими в цiй роботi. Показано можливостi методiв передбачати вищi вiрiальнi коефiцiєнти однокомпонентної системи твердих сфер. Запропоновано оцiнки для вiрiальних коефiцiєнтiв вiд одинадцятого до п’ятнадцятого. Передбачається, що вiрiальнi коефiцiєнти Bn вищого порядку нiж B₁₄, можуть зменшуватися з ростом n i можуть досягати негативних значень для великих n. Цi екстраполяцiйнi методи можуть бути використанi в iнших областях, де екстраполяцiя є важливою.